2022
DOI: 10.1007/s10668-022-02781-x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the integral development of agriculture and tourism on agricultural eco-efficiency: a case study of two river basins in China

Abstract: The integral development of agriculture and tourism heavily depends on natural resources, especially agricultural resources, and it also may contribute to the sustainability of agriculture. The sustainability of agriculture is usually measured by the agricultural eco-efficiency. The main objective of this paper is to demonstrate the impact of the agriculture and tourism integration on agricultural eco-efficiency, so as to reflect the role of the agriculture and tourism integration on promoting agricultural sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 94 publications
0
0
0
Order By: Relevance
“…In addition, tourism-driven poverty reduction can eliminate absolute poverty in rural areas, provide a good development environment for industrial development, promote the docking of tourism with agriculture, animal husbandry, and other related industries, form industrial interaction and linkage effects, and further promote the integration of agriculture and tourism. On the other hand, the integration of agriculture and tourism can promote the transformation and upgrading of the industry through the organic combination of agriculture and tourism, thus improving economic efficiency and achieving the purpose of eradicating poverty [8,50]. Agriculture and tourism are naturally complementary industries, with tourism being backwardly related to catering, accommodation, and handicrafts and forwardly related to agriculture.…”
Section: Hypothesismentioning
confidence: 99%
“…In addition, tourism-driven poverty reduction can eliminate absolute poverty in rural areas, provide a good development environment for industrial development, promote the docking of tourism with agriculture, animal husbandry, and other related industries, form industrial interaction and linkage effects, and further promote the integration of agriculture and tourism. On the other hand, the integration of agriculture and tourism can promote the transformation and upgrading of the industry through the organic combination of agriculture and tourism, thus improving economic efficiency and achieving the purpose of eradicating poverty [8,50]. Agriculture and tourism are naturally complementary industries, with tourism being backwardly related to catering, accommodation, and handicrafts and forwardly related to agriculture.…”
Section: Hypothesismentioning
confidence: 99%
“…Pulina et al [17] consider agritourism as a set of activities in which people combine tourism with agricultural production, services, and agricultural experiences that are beneficial to farmable yields and farm incomes. Wang et al [18] found that the integrated development of both agriculture and rural tourism relies heavily on natural resources, especially agricultural resources, which may also contribute to the sustainability of agriculture. Using the Yangtze River Basin and the Yellow River Basin in China as case studies, the article examines not only the economic but also the ecological effects of agritourism integration, providing insights into the development of regional policies for integrating agriculture and tourism [18].…”
Section: Rural Tourism Industry Integrationmentioning
confidence: 99%
“…Wang et al [18] found that the integrated development of both agriculture and rural tourism relies heavily on natural resources, especially agricultural resources, which may also contribute to the sustainability of agriculture. Using the Yangtze River Basin and the Yellow River Basin in China as case studies, the article examines not only the economic but also the ecological effects of agritourism integration, providing insights into the development of regional policies for integrating agriculture and tourism [18]. Santeramo et al [19] analyze the synergistic relationship between domestic tourism and the wine industry in Italy and give their answer to the question of how to use the advantages of grapevine agriculture to promote the integration of the local tourism industry and give some policy recommendations for its development.…”
Section: Rural Tourism Industry Integrationmentioning
confidence: 99%
“…( [23][24][25][26]. Moreover, it contributes to regional sustainability and environmentally friendly growth (Liu et al, 2023;Wang et al, 2022) [27,28]. Secondly, the research relating to its poverty alleviation effect has revealed that eliminating poverty by solely relying on agricultural production has natural shortcomings.…”
Section: Implementation Effect Of the Integrated Development Of Agric...mentioning
confidence: 99%